Air fry everything! - Laurence, Meredith (Walah!, LLC/Publishers, 2016)
Fry With Air is the ultimate cookbook that will take your air fryer to the next level, creating quick food and meals that burst with flavor and color without the added calories and fat. Recipes include Cherry Chipotle Chicken Wings, Asian Glazed Meatballs, including Korean BBQ Pork, Parmesan Chicken Fingers, Fish and "Chips," Coconut Shrimp, Roasted Vegetable Stromboli, Fried Green Beans, Mini Molten Chocolate Cakes and Fried Banana S'mores, plus much more.